Life cycle assessment of permanent magnet electric traction motors - Nordelöf, Anders; Grunditz, Emma; Lundmark, Sonja; Tillman, Anne-Marie; Alatalo, Mikael; Thiringer, Torbjörn (Transportation research. Part D, Transport and environment, 2019)
[Display omitted] •Climate change and human toxicity important in LCA of electrical traction machines.•Complete manufacturing range within 1.7–2.0 g CO2-eq./km for all studied motors.•Copper production is significant for toxicity impacts and effects on human health.•Design focus: energy efficiency, housings, end-windings, laminates and disassembly. Ongoing development of electrified road vehicles entails a risk of conflict between resource issues and the reduction of greenhouse gas emissions. In this study, the environmental impact of the core design and magnet material for three electric vehicle traction motors was explored with life cycle assessment (LCA): two permanent magnet synchronous machines with neodymium-dysprosium-iron-boron or samarium-cobalt magnets, and a permanent magnet-assisted synchronous reluctance machine (PM-assisted SynRM) with strontium-ferrite magnets. These combinations of motor types and magnets, although highly relevant for vehicles, are new subjects for LCA. The study included substantial data compilation, machine design and drive-cycle calculations. All motors handle equal take-off, top speed, and driving conditions. The production (except of magnets) and use phases are modeled for two countries – Sweden and the USA – to exemplify the effects of different electricity supply. Impacts on climate change and human toxicity were found to be most important. Complete manufacturing range within 1.7–2.0 g CO2-eq./km for all options. The PM-assisted SynRM has the highest efficiency and lowest emissions of CO2. Copper production is significant for toxicity impacts and effects on human health, with problematic emissions from mining. Resource depletion results are divergent depending on evaluation method, but a sensitivity analysis proved other results to be robust. Key motor design targets are identified: high energy efficiency, slender housings, compact end-windings, segmented laminates to reduce production scrap, and easy disassembly.